La retórica de los antiguos mexicanos como instrumento para su conversión al cristianismo - Pavón, Sandra Anchondo (Tópicos, Revista de Filosofía, 2013)
This work is about the General History of the Things of New Spain in its complete and definitive version known as the Florentine Codex of 1557. It is our belief that Sahagún formulated a three language vocabulary (based in Nebrija’s Latin-Spanish dictionary as well as the one made by his companion Alonso de Molina) and an encyclopedic dictionary (never concluded) influenced by Ambrosio Calepino’s style for his preaching of the Gospel project. Finally, the organization of his known History fulfilled with a treatise which proposed both: the recognition of the Mexican language as a classic and the recompilation of all the poetical and rhetorical works in order to withdraw the vocabulary as well as these villages’ life style before the Conquest.